2007
DOI: 10.1590/s0102-05362007000100024
|View full text |Cite
|
Sign up to set email alerts
|

Identificação dos constituintes químicos da fração volátil da Calendula officinalis produzida no Paraná

Abstract: A Calendula officinalis L., pertence à família Asteraceae, é originária da Europa e está aclimatada na região Sul do Brasil, onde vem crescendo o seu cultivo comercial para fins farmacêuticos e cosméticos. Suas inúmeras propriedades terapêuticas entre as quais antiinflamatória, cicatrizante e anti-séptica, justificam a grande procura desta planta pela população. O presente trabalho compara a composição química da fração volátil da cultura de calêndula aclimatada na região Noroeste do Paraná, com os dados da li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
(3 reference statements)
0
12
0
1
Order By: Relevance
“…δ-cadinene (22.53%), α-cadinol (20.40%) and epi-α-muurolol (12.87%). The analyses were performed by GC and GC-MS as described by Gazim et al (8).…”
Section: Disc Diffusion Methodsmentioning
confidence: 99%
“…δ-cadinene (22.53%), α-cadinol (20.40%) and epi-α-muurolol (12.87%). The analyses were performed by GC and GC-MS as described by Gazim et al (8).…”
Section: Disc Diffusion Methodsmentioning
confidence: 99%
“…Oleoresin of B. uniflora is a potential source of geranyllinalool, but the concentration of chemical compounds of essential oils could vary according to flower stage (Bertrand et al, 2006), soil composition (Gazim et al, 2007), and extraction technique (Bertrand et al, 2006). Jorge (2016) reported that the pressure increase from 150 to 200 bars of supercritical carbon dioxide increases the extraction of geranyllinalool from 11.72 to 21.52% in oleoresin.…”
Section: Discussionmentioning
confidence: 99%
“…The cultivation soil was evaluated for pH, macroand micronutrients, and granulometry according to Camargo et al (2009). The soil samples were collected at 20 cm depth from four different equidistant points 1 m away from the plant to obtain a compound sample (Gazim et al, 2007). This region has humid temperate climate (CFa) according to Köppen-Geiger classification, with hot humid summer, more intense winter and without dry season, and annual average temperature of 22°-23°C and monthly rainfall of 1400-1600 mm (Peel et al, 2007).…”
Section: Biological Materialsmentioning
confidence: 99%
“…These plants are widely cultivated in Guarapuava (Paraná state, Brazil) and used by local population and worldwide to treat several diseases. Ethnobotanical studies performed in some communities in the Paraná state mentioned these medicinal plants, among others, as frequently used by local populations (Jacoby et al 2002;Marchese et al 2004Marchese et al , 2009Gazim et al 2007;Mossi et al 2009). For example, M. ilicifolia is commonly consumed as a tea or mixed with Ilex paraguariensis (erva-mate) in the traditional beverage known as "Chimarrão."…”
Section: Introductionmentioning
confidence: 99%